The Relationship Of Peer Support And Self Control With Social Media Addiction - Puspita Bahridah; Riska Ahmad; Zadrian Ardi; Rezki Hariko (Universitas PGRI Yogyakarta, 2023)
Excessive use of social media is called social media addiction. The goal of this study was to find out how social media addiction and peer support for self-control affect SMA Negeri 5 Padang students. The descriptive correlational approach and quantitative approach are utilized in this study. A purposive sampling strategy is utilized in the sampling procedure. The study's findings demonstrate: 1) The moderate category includes peer support; 2) (S) self-control falls under the moderate category; 3) Social media addiction falls into the moderate category; 4) There is a correlation coefficient of 0.327 between peer support and social media addiction; 5) There is a correlation coefficient of 0.515 between self control and social media addiction; and 6) There is a correlation coefficient of 0.542 between peer support and self control and social media addiction. This demonstrates that social media addiction can be reduced with increased self-control and peer support. Keywords : peer support, self control, social media addiction